Shell-like structures in our cosmic neighbourhood - Einasto M; Heinamaki P; Liivamagi LJ; Martinez VJ; Hurtado-Gil L; Arnalte-Mur P; Nurmi P; Einasto J; Saar E (EDP SCIENCES S A, 2022)
Context. Signatures of the processes in the early Universe are imprinted in the cosmic web. Some of them may define shell-like structures characterised by typical scales. Examples of such structures are shell-like systems of galaxies, which are interpreted as a signatures of the baryon acoustic oscillations.Aims. We search for shell-like structures in the distribution of nearby rich clusters of galaxies drawn from the SDSS DR8.Methods. We calculated the distance distributions between rich clusters of galaxies and groups and clusters of various richness, searched for the maxima in the distance distributions and selected candidates of shell-like structures. We analysed the space distribution of groups and clusters that form shell walls.Results. We find six possible candidates of shell-like structures, in which galaxy clusters have the maximum in their distance distribution to other galaxy groups and clusters at a distance of about 120-130 h(-1) Mpc. Another, less probable maximum is found at a distance of about 240 h(-1) Mpc. The rich galaxy cluster A1795, which is the central cluster of the Bootes supercluster, has the highest maximum in the distance distribution of all other surrounding groups and clusters in our rich cluster sample. It lies at a distance of about 120 h(-1) Mpc. The structures of galaxy systems that cause this maximum form an almost complete shell of galaxy groups, clusters, and superclusters. The richest systems in the nearby universe, the Sloan Great Wall, the Corona Borealis supercluster, and the UrsaMajor supercluster, are among them. The probability that we obtain maxima like this from random distributions is lower than 0.001.Conclusions. Our results confirm that shell-like structures can be found in the distribution of nearby galaxies and their systems. The radii of the possible shells are larger than expected for a baryonic acoustic oscillations (BAO) shell (approximate to 109 h(-1) Mpc versus approximate to 120-130 h(-1) Mpc), and they are determined by very rich galaxy clusters and superclusters. In contrast, BAO shells are barely seen in the galaxy distribution. We discuss possible consequences of these differences.